Archaeology live! : 2004 - York Archaeological Trust for Excavation and Research (2001)
[Dt.:] Online-Tagebuch einer Ausgrabung (Lehrgrabung) der Jahre 2001 bis 2004 am römischen Legionslager in York/ Eboracum. Für die Jahre 2005 und 2006: http://www.yorkarchaeology.co.uk/live2005/liveframeset2.htm; http://www.yorkarchaeology.co.uk/live2006/liveframeset2.htm. - [Engl.:] Online diary about a training dig, which took place in the years 2001-2004 at the Roman legionary fortress in York/ Eboracum. For the years 2005 and 2006 see: http://www.yorkarchaeology.co.uk/live2005/liveframeset2.htm; http://www.yorkarchaeology.co.uk/live2006/liveframeset2.htm